Trends and Intellectual Structure of Halal Industry Research Based on Bibliometric and Network Visualization 2010–2024 - Judijanto, Loso (West Science Islamic Studies, 2026)
The halal industry has witnessed remarkable growth in recent years, emerging as a global economic force. This study employs bibliometric analysis and network visualization to explore the trends and intellectual structure of halal industry research from 2010 to 2024. By examining keyword co-occurrence, co-authorship, and country collaboration patterns, the study identifies key themes such as halal certification, supply chain transparency, halal tourism, and ethical considerations in animal welfare. Southeast Asia, particularly Indonesia and Malaysia, leads the field, with increasing collaboration across regions, including Western countries and non-Muslim-majority nations like Turkey, Australia, and South Korea. The study reveals an evolving research landscape, showcasing the integration of technology and sustainability into halal industry practices, and provides a roadmap for future scholarly exploration within this growing sector.